A neuronal enhancer network upstream of MEF2C is compromised in patients with Rett-like characteristics. (15th November 2018) - D'haene, Eva; Bar-Yaacov, Reut; Bariah, Inbar; Vantomme, Lies; Van Loo, Sien; Cobos, Francisco Avila; Verboom, Karen; Eshel, Reut; Alatawna, Rawan; Menten, Björn; Birnbaum, Ramon Y; Vergult, Sarah
Abstract: Mutations in myocyte enhancer factor 2C ( MEF2C ), an important transcription factor in neurodevelopment, are associated with a Rett-like syndrome. Structural variants (SVs) upstream of MEF2C, which do not disrupt the gene itself, have also been found in patients with a similar phenotype, suggesting that disruption of MEF2C regulatory elements can also cause a Rett-like phenotype. To characterize those elements that regulate MEF2C during neural development and that are affected by these SVs, we used genomic tools coupled with both in vitro and in vivo functional assays. Through circularized chromosome conformation capture sequencing (4C-seq) and the assay for transposase-accessible chromatin using sequencing (ATAC-seq), we revealed a complex interaction network in which the MEF2C promoter physically contacts several distal enhancers that are deleted or translocated by disease-associated SVs. A total of 16 selected candidate regulatory sequences were tested for enhancer activity in vitro, with 14 found to be functional enhancers. Further analyses of their in vivo activity in zebrafish showed that each of these enhancers has a distinct activity pattern during development, with eight enhancers displaying neuronal activity. In summary, our results disentangle a complex regulatory network governing neuronal MEF2C expression that involves multiple distal enhancers. In addition, the characterized neuronal enhancers pose as novel candidates to screen for mutations in neurodevelopmental disorders, such as Rett-like syndrome.